2009
DOI: 10.1182/blood-2008-12-196568
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of chronic lymphocytic leukemia: clinical and biologic features of 9 cases

Abstract: In chronic lymphocytic leukemia (CLL), spontaneous regressions are an exceptional phenomenon, whose biologic features are unknown. We describe 9 CLL patients who underwent a spontaneous clinical regression over an 11-year followup, despite a residual neoplastic clone detected by flow cytometry. CD38 and ZAP-70 were negative in all cases. Immunoglobulin heavy chain variable region (IgVH) genes, mutated in all 7 evaluable patients, were restricted to the VH3 family

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 26 publications
0
55
0
1
Order By: Relevance
“…Spontaneous clinical regression of CLL has been previously described in the literature, although a recent study suggested that a residual MBC population remains detectable by flow cytometry or molecular analysis in such patients. 36,37 While the three patients in our study with regression had no evidence of an absolute lymphocytosis, LAD, or splenomegaly at last follow-up, PB specimens were not available to evaluate for the presence of a persistent clonal B-cell population by flow cytometry. Continued follow-up is necessary to determine whether these patients will remain in clinical remission.…”
mentioning
confidence: 97%
“…Spontaneous clinical regression of CLL has been previously described in the literature, although a recent study suggested that a residual MBC population remains detectable by flow cytometry or molecular analysis in such patients. 36,37 While the three patients in our study with regression had no evidence of an absolute lymphocytosis, LAD, or splenomegaly at last follow-up, PB specimens were not available to evaluate for the presence of a persistent clonal B-cell population by flow cytometry. Continued follow-up is necessary to determine whether these patients will remain in clinical remission.…”
mentioning
confidence: 97%
“…The hypothesis for a key role of the immune system in combating cancer is further supported by clinical observations on spontaneous regressions of tumor in humans (Bodey, 2002;del Giudice et al, 2009;Oquiñena et al, 2009) and an increased risk of some cancer development in immunodeficient patients (Jagadeesh et al, 2012;Kubica & Brewer, 2012). It has also been shown that a presence of immune cell infiltrates in cancer tissues correlate with a better prognosis (Movassagh et al, 2004;Pagès et al, 2005;Wansom et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…These T cells express the activating receptor NKG2D, which is able to mediate the lysis of CLL cells expressing NKG2D ligands ("induced self" recognition) (Figure 1). Leukemia cells from most patients lack NKG2D ligands expression and are highly resistant to NK cell-mediated lysis, but NKG2D ligands www.intechopen.com expression may be induced in leukemia cells by treatment with trans-retinoic acid or histone deacetilases (HDACs) inhibitors, rendering leukemia cells susceptible to lysis by immune cells Del Giudice et al, 2009). The expansion of T cells has been associated with a better prognosis of CLL patients, supporting the hypothesis that the increase of T cells observed at diagnosis of CLL patients may be due, at least in part, to the expansion of anti-tumor T cells.…”
Section: Immune Surveillance Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…The natural history of stage A disease is generally indolent or only slowly progressive. However, it is less known that CLL may undergo spontaneous regression (Del Giudice et al, 2009). There are no data about the functional role of the immune system in these remissions; however the activation of immune system has been associated with spontaneous remissions in other types of cancers (Smyth et al, 2006;Swann et al, 2007).…”
Section: Immune Surveillance Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%